Preliminary exploration of finite element biomechanical preoperative planning for complex tibial plateau fractures - Zhi Xu; Yuwan Li; Shoujin Tian; Xing Xu; Hao Zhou; Min Yang (Scientific Reports)
Abstract The aim of this study was to compare the clinical outcomes, biomechanical performance, and cost-effectiveness of finite element planning (FEP) with those of traditional (Trad) methods in the treatment of complex tibial plateau fractures in middle-aged and elderly patients to ultimately optimize treatment protocols, improve surgical efficiency, and reduce the economic burden on patients. Sixteen patients with complex tibial plateau fractures were randomly divided into FEP and Trad groups, with eight patients in each group. The FEP group underwent preoperative finite element analysis for personalized surgical planning and dual-plate fixation; the Trad group participated in traditional preoperative discussions and underwent a multi-plate fixation. Perioperative and postoperative indicators were collected from both groups, and the stress distribution and displacement under different internal fixation modes were evaluated using finite element analysis. Additionally, a cost-effectiveness analysis was conducted to compare the total costs of internal fixation and hospitalization. The surgical times were significantly shorter in the FEP group than in the Trad group (170.00 ± 59.52 vs. 240.00 ± 59.04 min, p = 0.033), and patients in the Trad group had shorter times to ambulation (12.88 ± 0.99 vs. 14.25 ± 1.49 days, p = 0.047). There were no significant differences between the groups in terms of postoperative orthopaedic scores, mobility indices, fracture healing times, or radiological indicators. Biomechanical analysis revealed that the multiplate fixation mode provided a more uniform stress distribution, but this difference was not statistically significant. In the FEP group, the total costs of internal fixation (4772.25 ± 217.31 vs. 8991.88 ± 2811.25 yuan, p = 0.004) and hospitalization (34796.75 ± 9749.19 vs. 65405.14 ± 28684.80 yuan, p = 0.013) were significantly lower. While ensuring clinical effectiveness, FEP demonstrated greater cost-effectiveness by shortening the surgery time and reducing internal fixation costs. Although the multiplate fixation mode was biomechanically superior to the dual-plate mode, it did not result in significant clinical advantages and was more costly. FEP improves the economic efficiency of treatment for complex tibial plateau fractures in middle-aged and elderly patients and is recommended. This study has certain limitations, such as a small sample size and a short follow-up period. Thus, larger-scale studies with longer-term follow-up data are needed to further validate these findings and explore whether all patient populations can benefit from these practices or if the benefits are limited to specific groups, such as elderly patients or those with certain types of fractures.